2019
DOI: 10.23986/afsci.75600
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of grass-legume mixture for improvement of crop growth and reducing potential nitrogen loss in a boreal climate

Abstract: A three-year field experiment was established to assess intercropping for sustainable forage production in Finland. In split-plot design, fertilizer treatment with unfertilized control, organic fertilizer, and synthetic fertilizer was the main plot factor, and crop treatment with fallow, red clover (Trifolium pratense), timothy (Phleum pratense), and a mixture of red clover and timothy was the sub-plot factor. Dry matter, carbon and nitrogen yields in mixture plots were highest with relatively high N% and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Generally, the soil had lower NO 3 -N content and higher moisture content in the autumn than in the summer (Li et al, 2019). From summer to autumn, the relative abundances of Acidobacteria and Bacteroidetes increased, while that of Actinobacteria decreased.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Generally, the soil had lower NO 3 -N content and higher moisture content in the autumn than in the summer (Li et al, 2019). From summer to autumn, the relative abundances of Acidobacteria and Bacteroidetes increased, while that of Actinobacteria decreased.…”
Section: Discussionmentioning
confidence: 93%
“…Soil NH and NO were extracted with 2 M KCl and measured with Lachat QuickChem 8000 (Lachat Instruments, Milwaukee, WI, United States), soil pH and EC were determined in a 1:2.5 (w/w) soil–water mixture, and total C and N were determined with TruSpec Elemental Determinator (LECO, United States). The details were reported in Li et al (2019) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant diversity in the perennial mixtures increases the N 2 fixation mainly as a result of the non-legume species competition for N from soil (Carlsson and Huss-Danell, 2003;Rasmussen et al, 2012). For example, Li et al (2019) showed that an unfertilized timothy-red clover mixture had higher dry matter yield than N fertilized sole stands in Finland because through biological N fixation plants were able to utilize resources more efficiently. Dhamala et al (2017) concluded that perennial mixtures need to have non-legume species to maximally benefit from the N 2 fixation.…”
Section: Perennial Forage Mixturesmentioning
confidence: 99%
“…We aimed to disentangle the underlying mechanism of how the agricultural management regimes in these sub-boreal grasslands affect microbial communities and their capacity for N-cycling and how such changes may affect crop yield. Hence, we conducted an integrated analysis, including crop yield, soil properties and the composition of soil bacterial communities previously reported from the same field experiment [20,23], along with the abundance of several functional groups within the N-cycling communities. We specifically tested the hypotheses that i) the soil microbial communities mediate management effects on crop yield and the potential for both N retention and N 2 O sink capacity and ii) an increase in potential for N retention increases crop yield.…”
Section: Introductionmentioning
confidence: 99%